Dermis-retained breast dermo-glandular flap: a new surgical approach for granulomatous lobular mastitis - Huang, Junying; Sin, Tat-Hang; Nie, Longzhu; Zhou, Yidong; Zhang, Fan; Ma, Jia; Shi, Xiaoguang; Chen, Linlin; Niu, Kunying; Zhang, Xiaohui; Sun, Qiang; Huang, Hanyuan (Frontiers in Surgery, 2023)
Background: Granulomatous lobular mastitis (GLM) is characterized by nonspecific chronic inflammation concentrated in breast lobules. Surgical resection is one of the most common treatment options for GLM. On the basis of our previous use of Breast Dermo-Glandular Flap (BDGF), we designed a new surgical approach for GLM, especially for cases where the focus is close to the nipple. Here we describe this new treatment approach. Methods: In Peking Union Medical College Hospital (PUMCH) and Beijing Dangdai Hospital during January 2020—June 2021, we enrolled all 18 GLM patients who underwent surgery with the use of Dermis-Retained BDGF. All patients were women; most of the patients were 18–50 years old (88%); and the most common clinical manifestation of GLM was breast mass (60%). Then, we collected and analyzed data about the surgery and outcomes (drainage tubes moving time, relapse, patients’ shape satisfaction). We regarded GLM recurrence on the same side as relapse. If there was no complication and the patient’s satisfaction was excellent or good, we rated the surgery as successful. We recorded the occurrence of all common postsurgical complications of the breast. Results: The debridement area was 3–5.5 (4.3 ± 0.7)cm; surgery time was 78–119 (95.6 ± 11.6) min; and mean debridement time (27.8 ± 8.9 min ) was shorter than the time to obtain and transplant the flap (47.5 ± 12.9 min). Blood loss was less than 139 ml. As for bacterial culture, two patients had positive results, but they had no symptoms. No surgery-related complications happened. In terms of the outcomes, all of the drainage tubes were removed in less than 5 days, and only one patient experienced relapse after 1 year of surgery during the follow-up. The patients’ satisfaction with the breast shape was as follows: excellent (50%), good (22%), acceptable (22%), and poor (6%). Conclusion: For GLM patients refractory to conservative therapy or former unsatisfactory surgical management whose lesion is in the vicinity of the nipple and larger than 3cm, Dermis-Retained BDGF is a suitable approach to fill the after-debridement defect below the nipple-areola and achieve a relatively satisfactory cosmetic outcome.